2021
DOI: 10.1172/jci.insight.151349
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive T cell receptors with shared germline-like α chains in type 1 diabetes

Abstract: Conflict of interest: TMB declares that he is a consultant for Repertoire Immune Medicines and has a collaborative grant (in-kind services) with Adaptive Biotechnologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(76 citation statements)
references
References 63 publications
5
71
0
Order By: Relevance
“…The two TCRs, which we will term: “Lower Avidity TCR” or L-TCR, and “Higher Avidity TCR” or H-TCR, were found to trigger significantly different rates of proliferation across a range of peptide doses, consistent with their reported avidity (Fig. 3, C)(43). As the highest peptide dose reliably produced efficient proliferation in all donors tested, we used this dose for activation of PTPN22 edited cells.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…The two TCRs, which we will term: “Lower Avidity TCR” or L-TCR, and “Higher Avidity TCR” or H-TCR, were found to trigger significantly different rates of proliferation across a range of peptide doses, consistent with their reported avidity (Fig. 3, C)(43). As the highest peptide dose reliably produced efficient proliferation in all donors tested, we used this dose for activation of PTPN22 edited cells.…”
Section: Resultsmentioning
confidence: 76%
“…Previous work has detailed the sequencing of multiple TCRs from T1D patients that are reactive against the pancreatic islet autoantigen IGRP (42, 43), and recent work has shown that gene edited primary human T cells can be rendered antigen specific through the lentiviral delivery of these TCRs prior to electroporation with RNPs (50). To study the impact of PTPN22 loss of function on antigen specific TCR responses, we transduced human cord blood CD4 T cells with lentiviral vectors (LV) encoding for alternative TCRs that respond to the same 20mer epitope of IGRP when presented by HLA-DRB1 04:01; and subsequently modified these LV transduced populations using the HDR-based gene editing (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NGS dataset of GSE182870 [22] were obtained from the National Centre of Biotechnology Information (NCBI) Gene Expression Omnibus database (GEO, https://www.ncbi.nlm.nih.gov/geo/) [23]. GSE182870, which comprises a total of 780 samples, including 600 T1DM samples, and 180 normal control samples, was based on the platform of the GPL18573 Illumina NextSeq 500 (Homo sapiens).…”
Section: Methodsmentioning
confidence: 99%